Análisis de contenidos del complejo de comunicación virtual Sexo Sentido en el proceso de promover la educación sexual en Riobamba periodo septiembre 2020 marzo 2021. - Lema Lema, María Alejandra (2024)
ABSTRACT: The evolution in communication has been growing by leaps and bounds, look back a few years and verify the progress from analog to the present with the management of technology and how artificial intelligence is rapidly approaching. The main objective of this research is to examine the contents of the virtual communication complex Sexo Sentido in the process of promoting sex education in Riobamba from September 2020 to March 2021. The methodology used was the mixed method with diagnostic research type, with synchronous scope, as well as interviews and research of bibliographic sources that help to support this work and that were previously generated with non-experimental design. The population was obtained from the information of the content distribution platforms that comprise it. In this case, Facebook has 101 publications, Instagram has 56, YouTube has 7, and the website has 13 publications, of which 11 are podcasts that were analyzed in the external application iVoox, in which interviews directed to experts and review tabs were conducted. As a result, content analysis was essential in developing new information. Because it is considered a tool that allows access to first-hand information, reaching new knowledge. In conclusion, when determining the types of content used by Sexo Sentido, it is verified that the infographics used managed to increase visibility in digital media publications, the videos transmitted clear, entertaining, informative messages, and podcasts provided accessibility to more people through audio and written texts on the website allowed to know about the experiences of their followers according to the topics discussed on sex education, making them participants and showing that they are interested in the communication products created by this community. All this is thanks to the planning and strategies applied by the members of Sexo Sentido to inform young people and adults about the importance of leaving taboos aside, allowing them to learn without prejudice about topics related to sexuality, but above all, that it is not wrong to want to discover new things and what better if it is with expert guests in this area